MENINGKATKAN KEMAMPUAN KOMUNIKASI (COMMUNICATION SKILL) DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN SAINTIFIK DENGAN MEMANFAATKAN MEDIA INFOGRAFIS - RIZAWATI RIZAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This research is motivated by the low communication skills and student learning outcomes in class XI MIPA 1 SMAN 1 Bengkulu Utara. Communication skills are one of the 21st century competencies that must be mastered by students. This needs to be a concern and find solutions and strategies in learning. One strategy that can be done by a teacher is through scientific learning by utilizing infographic media. This study aims to describe the learning process through the application of a scientific approach by utilizing infographic media, to describe the process of improving communication skills and student learning outcomes in Biology subjects in class XI MIPA 1 SMAN 1 Bengkulu Utara in the 2021/2022 academic year. This type of research is classroom action research. This research has an action procedure that begins with planning, action, observation, and reflection. This research took place in three cycles with the subjects of 31 students of class XI MIPA 1 in the odd semester of the 2021/2022 academic year. The results showed that there was an increase in communication skills and student learning outcomes through scientific learning by utilizing infographic media. This is indicated by the results of the study that the scientific learning process runs according to the sequence of scientific steps in the first cycle carried out 78%, in the second cycle increased to 88% and in the third cycle increased to 95%. Along with the improvement of the scientific learning process by utilizing infographic media, there was an increase in students' communication skills from cycle I as many as 5 students, cycle II to 8 students and cycle III to 14 students already exceeding the success indicator, namely 10 students. Along with the improvement of the scientific learning process by utilizing infographic media, there was an increase in students' communication skills from cycle I there were 5 students, cycle II became 8 students and cycle III became 14 students, exceeding the success indicator, namely 10 students. Student learning outcomes have increased starting in the first cycle, namely 9.68% of students who achieved the KKM, in the second cycle it became 45.16% and in the third cycle it increased to 77.42%Thus, it can be concluded that scientific learning by utilizing infographic media can improve communication skills and student learning outcomes of class XI MIPA 1 SMAN 1 Bengkulu Utara Odd Semester for the 2021/2022 Academic Year. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya kemampuan komunikasi dan hasil belajar siswa di kelas XI MIPA 1 SMAN 1 Bengkulu Utara. Kemampuan komunikasi menjadi salah satu kompetensi abad 21 yang harus dikuasai oleh siswa. Hal ini perlu menjadi perhatian dan dicarikan solusi dan strategi dalam pembelajarannya. Salah satu strategi yang dapat dilakukan oleh seorang guru adalah melalui pembelajaran saintifik dengan memanfaatkan media infografis. Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran melalui penerapan pendekatan saintifik dengan memanfaatkan media infografis, mendeskripsikan proses peningkatan kemampuan komunikasi ( communication skill ) dan hasil belajar siswa pada mata pelajaran Biologi di kelas XI MIPA 1 SMAN 1 Bengkulu Utara Tahun Pelajaran 2021/2022. Jenis penelitian ini adalah penelitian tindakan kelas. Penelitian ini memiliki prosedur tindakan yang diawali dengan merencanakan, tindakan, observasi, dan refleksi. Penelitian ini berlangsung selama tiga siklus dengan sabjek 31 siswa kelas XI MIPA 1 pada semester ganjil Tahun Pelajaran 2021/2022. Hasil penelitian menunjukkan terjadi peningkatan kemampuan komunikasi dan hasil belajar siswa melalui pembelajaran saintifik dengan memanfaatkan media infografis. Hal ini ditunjukkan dengan hasil penelitian bahwa proses pembelajaran saintifik berjalan sesuai dengan urutan langkah-langkah saintifik di siklus I terlaksana 78%, pada siklus II meningkat menjadi 88% dan pada siklus III meningkat menjadi 95%. Seiring peningkatan proses pembelajaran saintifik dengan memanfaatkan media infografis terjadi peningkatan pada kemampuan komunikasi siswa dari siklus I sebanyak 5 orang siswa, siklus II menjadi 8 orang siswa dan disiklus III menjadi 14 orang siswa sudah melebihi dari indikator keberhasilan yakni 10 orang siswa. Hasil belajar siswa mengalami peningkatan yang bermula di siklus I yakni 9,68% siswa yang mencapai KKM, pada siklus II menjadi 45,16% dan pada siklus III meningkat menjadi 77,42%. Dengan demikian dapat disimpulkan bahwa pembelajaran saintifik dengan memanfaatkan media infografis dapat meningkatkan kemampuan komunikasi dan hasil belajar siswa kelas XI MIPA 1 SMAN 1 Bengkulu Utara Semester Ganjil Tahun Pelajaran 2021/2022.